SCHEDULING APPOINTMENTS OF TRUCK ARRIVALS AT CONTAINER TERMINALS - Riaventin, Veterina Nosadila; Kim, Kap Hwan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In container terminals at hub ports, each trucking company delivers a large number of containers every day. The truck drivers for the delivery operation may experience long waiting times when they arrive at peak hours. To reduce congestion, this study assumes that the container terminal charges a congestion fee (appointment charge), which depends on the expected staying time of trucks in the terminal, to control truck arrival times. This study proposes a scheduling method for appointments that takes into account the appointment charge, waiting time, operation cost of trucks, and number of available trucks. This study introduces a mathematical formulation and heuristic algorithms for solving the problem within a reasonable computational time. The heuristic algorithms consist of Phase 1, which solves a transportation problem, and Phase 2, which generates a solution respective of that obtained via Phase 1 such that the capacity constraint of the trucks is satisfied. Numerical experiments are conducted to test the heuristic approaches.